Gaining Loyalty Intention in Virtual Reality Tourism: A Lesson from US Tourists - Faezeh Mohagegh; Aditia Sobarna; Alfia Zahraputeri (Jurnal Internasional Penelitian Bisnis Terapan, 2022)
This study (1) evaluates the loyalty intention model in virtual reality (VR) tourism, covering VR content quality, VR system quality, and VR satisfaction as its determinants, and (2) assesses the moderating role of demographic factors in the formation of the loyalty intention model. Data was collected using an online survey from 288 US tourists that have experienced visiting tourist destinations via VR. The data analysis, using partial least square, notes that VR content quality was the strongest predictor of tourist satisfaction and loyalty intention. Next, the multi-group analysis reveals that the demographic factors tend to insignificantly moderate the relationships between tested constructs in the loyalty intention model.